Leveraging Optical Coherence Tomography and Angiography Artifacts to Identify Clinicopathological Correlates in Macular Disorders - Luca Scuderi; Serena Fragiotta; Chiara Ciancimino; Marco Mafrici; Marco Mazzola; Monica Varano; Tommaso Rossi; Mariacristina Parravano (Photonics, 2024)
Optical Coherence Tomography (OCT) and Optical Coherence Tomography Angiography (OCTA) are pivotal imaging techniques in diagnosing and managing macular disorders, providing high-resolution cross-sectional images of the retina. Although OCT artifacts are often deemed undesirable, they can paradoxically offer valuable insights into retinal pathology. This review explores the potential of OCT and OCTA artifacts to serve as indicators of pathological correlates in various macular conditions. The study emphasizes the importance of recognizing and leveraging these artifacts to refine clinicopathologic correlates characterizing several macular disorders, including age-related macular degeneration, diabetic retinopathy, and retinal vascular occlusive disease. OCT artifacts can reflect the ultrastructure and composition of pathological features, and their recognition can thus expand the understanding of the pathogenesis and improve the diagnostic interpretation of macular disorders. With the widespread use of OCT and OCTA technologies, identifying artifacts with clinicopathologic significance is of paramount importance and may have significant implications for management and prognosis.